Legal Analysis of Buying And Selling Caused by Fear of Missing Out Based on Imam Syafii’s Perspective - Al-Kholis, Muhammad Asyraf; Ardiansyah, Ardiansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Fear of Missing Out (FOMO) action is a social media that displays social status and flaunts success in life which often drives fear, anxiety, and behavior in individuals. The FOMO behavior from a buying and selling perspective has been an opportunity. The fears and anxieties of FOMO actors can stimulate individual consumption and shopping behavior by formulating certain marketing strategies. Islam itself has explained the rules in buying and selling activities, including explaining the law of buying and selling from the point of view of Imam Syafii. This study adopted a qualitative method. The Imam Syafi’i school says that when an aqad (transaction) has 3 (three) pillars (as) An-Nawawi said in Syarh Muhadzab, one of them is sighat. Meanwhile, the sale and purchase law with Fear of Missing Out is considered invalid because it removes one of the pillars of the contract, namely sighat, a clause of intent based on the purpose of buying and selling. The purpose of this study is to find out how the legal aspects of buying and selling where the perpetrators are influenced by the FOMO phenomenon from an Islamic perspective, especially Imam Syafi’i. The results of the study show that there is no fraud (free from deception or tadlis or deception or taghrir) as long as the buyer and seller both have sincerity, especially Imam Shafi’i. The results of the study show that there is no fraud (free from deception or tadlis or deception or taghrir) as long as the buyer and seller both have sincerity, especially Imam Syafi’i.